Dari Umayyah Sampai Utsmani: Lintasan Sejarah Kekhalifahan Pasca Ar Rasyidin - Basor, Saepul; Sugiarto, Deri (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Since the end of the Ar-Rashidin Caliphate, the Muslim world has known at least three Caliphates namely the Umayyads, Abbasids and Ottomans. However, there was an empty period of the Caliphate since the collapse of the Abbasids in 1258 AD. The power in the Muslim world which was later re-recognized as the Caliphate was Ottoman. The Ottoman ascension to the position of the Caliphate took place in 1517 AD. The Ottoman Caliphate itself ended in 1924 AD. Since the end of the Ottomans, the institution of the Caliphate in the Muslim World has been empty until now. When the idea of the Caliphate re-echoed, the discussion of the history of the Caliphate became important again. The following article aims to describe the trajectory of the history of the Caliphate after the end of the Ar Rashidin Caliphate. This study uses historical methods. The results of this study are expected to provide useful historical information in an effort to better understand the reality of Muslim life, especially from its historical aspects, especially in the topic of the Caliphate. Keywords: Umayyad, Abbasid, Ottoman, caliphate, Muslim history